Meta Analysis: Effects of Supervision Support, Feedback, and Training on Utilization of Routine Health Information System in Health Workers - Lestari, Dinta; Tamtomo, Didik; Murti, Bhisma (Journal of Health Policy and Management, 2023)
Background: Routine health information is an important pillar in health planning, decision making, and improving health programs, as well as providing effective and efficient health services. This study aims to estimate the magnitude of the influence of supervision support, feedback, and training on the use of routine health information systems (SIKR), through a meta-analysis of primary studies conducted by previous researchers. Subjects and Method: This study is a systematic review and meta-analysis using the PRISMA flow chart and the PICO model. Population: health workers. Intervention: there is supervision support, there is feedback, and there is training. Comparison: no supervision support, no feedback, and no training. Outcome: Utilization of SIKR. The online databases used are Google Scholar, PubMed, and ProQuest with the keywords (Routine Health Information Utilization” OR “Management Health Information System”) AND (“Supportive Supervision” OR “Regular Supervision”) AND (Feedback OR “Regular Feedback ”) AND Training OR “HMIS Training” AND “Health Worker” OR “Health Professionals” AND “Cross sectional” AND aOR. There were 14 cross-sectional studies published in 2013-2023 that met the inclusion criteria. Analysis was performed with RevMan 5.3. Results: A meta-analysis was carried out on 14 articles with a cross-sectional study design from Ethiopia on health workers with a sample size of 6,088. The results of the meta-analysis showed that health workers who received supervised support 1.77 times to utilize SIKR compared to those who did not receive supervised support (aOR= 1.77; 95% CI= 1.21 to 2.59; p=0.003), health workers who received feedback 2.15 times to using CIC compared to those who did not receive feedback (aOR= 2.15; 95% CI= 1.29 to 3.58; p=0.003), and health workers who received training 2.65 times to use CIC compared to those who did not receive training (aOR= 2.65; CI 95 %= 1.70 to 4.13; p<0.001). Conclusion: There is support for supervision, feedback/feedback, training/training can increase the utilization of routine health information systems.   Keywords: Supervision support, feedback, training, use of SIKR. Correspondence: Dinta Lestari, Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: dintalestari99@gmail.com. Mobile: 082183568772